IMPLEMENTATION OF THE FINAL DISPOSAL SITE (LANDFILL) DIVERSION POLICY BY THE ENREKANG DISTRICT ENVIRONMENTAL AGENCY (STUDY ON TPA ALLA DISTRICT) - Hafish, Ahmad; Sakawati, Herlina; Rukmana, Novayanti Sopia (Jurnal Aktor, 2025)
This study aims to determine the Implementation of Landfill Transfer Policy by the Environmental Office in Alla District, Enrekang Regency to achieve this goal, researchers usedata collection techniques through observation, interviews, and documentation. The data obtained from the results of the study were processed using qualitative analysis to determine the Implementation of Landfill Transfer Policy by the Environmental Office in Alla District, Enrekang Regency. The results showed that the implementation of the Landfill Transfer Policy by the Enrekang District Environmental Office (Alla Sub-District Landfill Study) was not effectively implemented in the Landfill Transfer in Alla District. Based on the Policy Implementation indicators, among others: Communication, the implementation of the Landfill (TPA) relocation policy has been going well. Resources, involvement of many parties and provision of transport fleets.HoweveritneedstobeoptimizedonDisposition,andOrganizationalStructure.Disposition, not yet the maximum realization of diversion in the transportation of waste. The organizational structure, Standard Operating Procedures (SOP) of the Environment Agency have not been fully understood by the public regarding waste transportation management